The work of a student to solve the equation 2(3x − 4) = 8 + 2x + 4 is shown below:
Step 1: 2(3x − 4) = 8 + 2x + 4
Step 2: 5x − 6 = 12 + 2x
Step 3: 5x − 2x = 12 + 6
Step 4: 3x = 18
Step 5: x = 6
In which step did the student first make an error and what is the correct step?
Step 2; 6x − 6 = 2(6 + x + 2)
Step 2; 6x − 8 = 12 + 2x
Step 3; 5x − 2x = 12 − 6
Step 3; 5x + 2x = 12 + 6

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

please help me

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.